Structural breaks and fiscal sustainability of the Indonesian government budget - Ivantia S. Mokoginta; Ria Marisa Stephanie (Universitas Islam Indonesia, 2015)
The purpose of this study is to identify government policy regimes or structural breaks as indicated by significant changes in debt to GDP ratio and to identify fiscal sustainability in Indonesia from 2000 to 2013. Using Fiscal Reaction Functions framework and Smooth Transition Regression, the study found two structural breaks following the three regimes. Foreign debt repayment dominates the government policy during Regime I. Fiscal consolidations and discipline such as reducing energy subsidies in 2002 and 2005, managing debt portfolio and increasing government revenues were dominant during Regime II. In Regime III, the government increases domestic debt, particularly to finance stimulus package. This study also found that the Indonesian fiscal is unsustainable during the period of study. Overall, the findings seem to suggest that managing government debt through fiscal consolidations, foreign debt repayment and debt portfolio management is not sufficient to achieve long-term fiscal sustainability.